ANTIPYRETICS EFFECT OF ETHANOL EXTRACT OF PARE LEAVES (Momordica charantia L.) ON MALE WHITE RAT (Rattus norvegicus) - polii, elisabeth (PHARMACON, 2024)
Bitter melon (Momordica charantia L.) is a plant that contains flavonoids. Based on previous studies, it has been reported that flavonoid compounds have antipyretic activity. The aim of this study is to test the antipyretic effect of bitter melon leaf extract (Momordica charantia L.). This study uses a laboratory experimental research design employing male white rats (Rattus norvegicus) as the test subjects. Bitter melon leaf extract was administered at different doses, namely 3.6 mg, 7.2 mg, and 14.4 mg. Each rat was induced to have a fever with a 0.2 ml intramuscular dose of the DPT vaccine. Temperature measurements were taken before and after induction for 2-3 hours and every 30 minutes until the 180th minute. The data obtained were analyzed using ANOVA and LSD tests. The research results indicate that the ethanol extract of bitter melon leaves (Momordica charantia L.) has an antipyretic effect that can lower the body temperature in male white rats (Rattus norvegicus) at a dose of 3.6 mg.